Pembrolizumab Combined With GDP Regimen Inducing Sustained Remission in Histiocytic Sarcoma: A Case Report - Jinjie Gao MD; Min Li MD; Cuiling Liu MD; Hongmei Jing MD (SAGE Publishing, 2024)
Histiocytic sarcoma (HS) is a rare hematopoietic neoplasm with an aggressive clinical course and a poor response to conventional chemotherapy. Currently, no standard treatment paradigms are available. Herein, we present a case of de novo HS treated with pembrolizumab combined with a GDP regimen (gemcitabine, cisplatin, and dexamethasone) that resulted in sustained complete remission with progression-free survival exceeding 4 years. Immunohistochemical analysis demonstrated significant overexpression of programmed death ligand 1 (PD-L1) on biopsy samples. Additionally, fluorescence in situ hybridization (FISH) with a JAK-2 probe indicated 9p24.1 amplification, suggesting reliance on the JAK-STAT pathway. Polymerase chain reaction (PCR) analysis did not reveal any BRAF-V600 mutations. Consequently, an immune checkpoint inhibitor (ICI) was administered alongside chemotherapy, resulting in sustained complete remission and progression-free survival for over 4 years. Our findings suggest that a combination of ICI and chemotherapy could represent a promising therapeutic approach for HS.